Enabling Music and Journalism Students To Respond Positively To Adversity In Work After Graduation: A Reconsideration Of Conventional Pedagogies - Latukefu, Lotte; Burns, Shawn; O'Donnell, Marcus; Whelan, Andrew (Journal of University Teaching and Learning Practice, 2014)
Elite classical music programs continue to focus teaching in Western Classical traditions where the emphasis is on technical virtuosity in instrumental or vocal performance. In this paper we discuss group activities and assessments used in two Creative Arts disciplines (Performance and Journalism), at an Australian regional university, as examples of subjects which provide ‘real world’ experience in order to promote resilience and tenacity in students. We incorporate narratives collected from students in performance and journalism to illustrate the value of recreating the complex division of labour of real world art practice, famously described by Becker (1982), as part of the musical learning experience. The paper concludes with reflections on how collaborative assessments/teaching activities can be developed to ensure the delivery of resilience and tenacity as a threshold learning outcome in a classical music course.